Pemberdayaan Masyarakat Untuk Pelestarian Kain Tenun Cagcag Sebagai Warisan Budaya di Desa Pejeng Kangin Gianyar Bali - Agus Darma Yoga Pratama; I Gusti Ayu Agung Dian Susanthi; Ni Made Rai Juniariani (Warmadewa Press, 2025)
Tenun Cagcag is one of Bali's cultural heritage items that holds high aesthetic, historical, and spiritual value. The production of this weaving is carried out traditionally using handlooms (not machines) and is passed down through generations, primarily by Balinese women. The advent of modernization and shifting interests among the younger generation threaten the continuity of weaving skills. One active group in preserving this craft is Kelompok Tenun Merak Mas in Pejeng Kangin Village, Gianyar. This group faces several challenges, such as limited product innovation, conventional marketing methods, and unorganized financial management. On the other hand, there is a market opportunity arising from global trends favoring ethnic products based on local culture. To address these challenges and capitalize on these opportunities, community service activities (PKM) are conducted through an empowerment approach, which includes training in product diversification, creating a visual catalog, enhancing digital literacy, and training in cash flow recording and bilingual marketing promotions. This program supports the preservation of local culture and encourages the strengthening of community economies through innovation and culture-based promotional strategies. The results of this program include improvements in production with a 40% increase in sales, advancements in marketing through the use of social media as a promotional tool featuring product catalogs, and enhancements in business management with established cash flow from sales. The application of technology and innovation, both hard and soft, has proven relevant and can be directly implemented by the partners. Thus, cultural heritage like Tenun Cagcag not only remains preserved but also adapts and competes in the dynamics of the modern market.